Assessing the predictive value of clinical factors to pathological complete response for locally advanced rectal cancer: An analysis of 124 patients - Zhou, Chaoxi; Wang, Kanghua; Zhang, Xiaoxiao; Xiao, Yuting; Yang, Congrong; Wang, Jun; Qu, Fuyin; Wang, Xuan; Liu, Ming; Gao, Chao; Xiao, Linlin; Wu, Fengpeng (Frontiers in Oncology, 2023)
Purpose: To investigate the clinical factors affecting pathological complete response (pCR) after neoadjuvant chemoradiotherapy (nCRT) in locally advanced rectal cancer (LARC). Methods: Clinical data of 124 LARC patients treated with nCRT and surgery in the fourth Hospital of Hebei Medical University from 2014 to 2019 were retrospectively analyzed. In this study, univariate analysis and logistic dichotomous multivariate regression analysis were used to study the clinical factors affecting pCR, and the receiver operator characteristic curve (ROC) analysis was used to further verify the accuracy of partial indexes in predicting pCR. Results: Of the 124 enrolled patients, 19 patients (15.32%) achieved pCR. Univariate analysis showed that the number of cycles of consolidation chemotherapy, serum carcino-embryonic antigen (CEA) level before treatment, MRI longitudinal length of tumor, and extramural vascular invasion (EMVI) were statistically correlated with pCR. ROC analysis of the longitudinal length of tumor measured by MRI showed that the area under the curve (AUC) value, sensitivity and specificity were 0.735, 89.47% and 48.57% respectively, and the optimal cut-off value was 5.5cm. The ROC analysis showed that the AUC value, sensitivity and specificity of pCR prediction using CEA were 0.741, 63.16% and 90.48%, respectively, and the optimal cut-off value was 3.1ng/ml. Multivariate results showed that the number of cycles of consolidation chemotherapy, serum CEA level before treatment, and EMVI were independent predictors of pCR. Conclusion: The number of cycles of consolidation chemotherapy, serum CEA level before treatment, and EMVI may be important determinants of LARC patients to reach pCR after nCRT.